Employee involvement effect on reducing job stress - Rezwan Ullah; Syed Zubair Ahmad; Amir Khan (Journal of Contemporary Economic and Business Issues, 2019)
This study has adopted the quantitative research approach for collecting data from different branches of the Bank of Khyber that are operating in the vicinity of the Saddar region, Peshawar city of Khyber Pakhtunkhwa province of Pakistan. The sample size consists of 60 employees. A total of 18 questions were asked based on the 5-point Likert scale responses. In order to perform numerous procedures, SPSS is used to analyse statistical tests in this study. Regression analysis is employed to test the hypothesis. Employee participation in the organization improves the overall productivity and contributes to organizational improvement. Job stress has a negative influence on the employee job performance. The results indicate that there is a negative and significant relationship between the employee's involvement and employee job stress. Although job stress is a negative phenomenon and may have a positive impact on the performance of the employees and eventually the organization.
Keywords: J11; J24; J28; 330; employee involvement; job stress; employee performance; employee empowerment; stress at work